Language as an Object of Philosophical Analysis - Pavilionis, Rolandas (Problemos, 1970)
The paper deals with the two questions: 1. what motivated language becoming an object of philosophical analysis, and 2. what are the consequences of such an analysis. Informal considerations on indeterminateness (vagueness of meanings, firstly, and of verbal expressions, secondly, constitute the answer to the first question. The answer to the second one is provided by a short analysis of the status and interrelation of natural, scientific and artificial languages. The author contends that indeterminacy of meaning is a natural consequence of the process of acquisition of meanings (information) in the system comprising both verbal and non-verbal meanings. Indeterminateness (vagueness) of verbal expressions on the other hand is treated as a natural consequence of the mechanism of language acquisition: many different meanings are coded by one and the same verbal expression there being no one-to-one correspondence between the class of meanings and that of verbal forms representing them. The interrelation between natural, scientific and artificial languages consequently is viewed in terms of the analysed phenomenon of indeterminateness, or rather in terms of increasing determinateness of verbal expressions.